2016
DOI: 10.1099/jgv.0.000333
|View full text |Cite
|
Sign up to set email alerts
|

PB2 subunit of avian influenza virus subtype H9N2: a pandemic risk factor

Abstract: Avian influenza viruses of subtype H9N2 that are found worldwide are occasionally transmitted to humans and pigs. Furthermore, by co-circulating with other influenza subtypes, they can generate new viruses with the potential to also cause zoonotic infections, as observed in 1997 with H5N1 or more recently with H7N9 and H10N8 viruses. Comparative analysis of the adaptive mutations in polymerases of different viruses indicates that their impact on the phylogenetically related H9N2 and H7N9 polymerases is higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 47 publications
(60 reference statements)
4
12
0
Order By: Relevance
“…These results demonstrate a synergistic between sites within a single protein and sites in different proteins; in other words, the polygenic nature of IAV virulence in mice. This is consistent with the observations from various experimental studies, such as the ones that demonstrate intra-protein synergy in PB2 [3237], PA [15], and NS1 [38, 39], and inter-protein synergy that involves combinations of PB2, PB1, PA, HA or NA [16, 40-46].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results demonstrate a synergistic between sites within a single protein and sites in different proteins; in other words, the polygenic nature of IAV virulence in mice. This is consistent with the observations from various experimental studies, such as the ones that demonstrate intra-protein synergy in PB2 [3237], PA [15], and NS1 [38, 39], and inter-protein synergy that involves combinations of PB2, PB1, PA, HA or NA [16, 40-46].…”
Section: Discussionsupporting
confidence: 92%
“…The critical role of PB2 in determining virulence in mice have been indeed highlighted for various strains, including H3N2 [44, 47], H5N1 [32-34, 48, 49], H5N8 [36, 50], H7N9 [5155], H9N2 [35, 37, 55, 56] and H10N8 [55]. Among the top 20 sites in PB2 for PART models, sites 627 and 701 have been repeatedly shown to affect IAV virulence in mammals including mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, comparison with other AIVs indicated that the effect of these mutations on polymerase activity is most distinct when introduced into the PB2 subunit of H9N2 virus or into H9N2‐related PB2. Our observations support the concept that H9N2‐like PB2 enhances the potential of an avian AIV to adapt to a mammalian host and highlight it as a potential pandemic risk fact (Sediri et al, ). Hence, these studies suggest that the gene constellation with G1‐like M and PB2 is involved in mammalian adaptation of the AIVs.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, this study seeks to evaluate the virulence the H5 reassortants contained genotype S or H H9N2 subtype AIV whole set of internal gene in mice, while the parental H5 viruses whose internal genes derive from H5 subtypes AIV or part from H9N2 in the previous study. It is possible that changes in the biological properties of the virus depend on the specific genomic background (Bi et al, 2015;Sediri, Thiele, Schwalm, Gabriel, & Klenk, 2016). H9N2 has generated numerous genotypes via genetic reassortment with other AI subtypes including H5 and H7, had circulated in China (Guan, Shortridge, Krauss, & Webster, 1999;Zhang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…HA and NA antigens of influenza A viruses continue to mutate or reassort with the potential to cause severe seasonal influenza epidemic or pandemic. Currently, strains of influenza type A viruses with potential to cause pandemic include H5N1, H7N9 (Imai et al, 2013;Uyeki and Cox, 2013;Lam et al, 2015), H9N2 (Sediri et al, 2015), and H10N8 (Chen et al, 2014). While surveillance of these emerging influenza A viruses in human, swine, and birds intensifies, there is the need to monitor climate for El Niño events, which modulate precipitation and promote viral transmission.…”
Section: Discussionmentioning
confidence: 99%